2018
DOI: 10.1007/s10266-018-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the preventive efficacy of three dentin tubule occlusion methods against discoloration caused by triple-antibiotic paste

Abstract: The aim of this in vitro study was to evaluate the preventive efficacy of three dentin tubule occlusion methods against discoloration caused by triple-antibiotic paste (TAP). Sixty extracted human incisors were sectioned, and the access was opened. The specimens were randomly allocated to the following four groups (n = 15): bonding application (BD), teethmate desensitizer (TM), Nd:YAG laser application (LS), and no surface treatment (control, C). Specimens were discolored with TAP over a period of 3 weeks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Our current study showed that both high and low concentrations of DAP and TAP demonstrated a significant increase in color change at the majority of time points. However, only 1,000 mg/mL TAP demonstrated consistent and significant discoloration that was clinically perceivable (ΔE > 3.7) regardless of adhesive use, which generally agrees with previous studies [ 13 22 34 ]. Therefore, the null hypothesis was rejected because the moderate and low concentrations of hydrogel-based DAP and TAP medicaments did not cause clinically perceivable tooth discoloration at all measured time points regardless of the use of an adhesive bonding agent.…”
Section: Discussionsupporting
confidence: 92%
“…Our current study showed that both high and low concentrations of DAP and TAP demonstrated a significant increase in color change at the majority of time points. However, only 1,000 mg/mL TAP demonstrated consistent and significant discoloration that was clinically perceivable (ΔE > 3.7) regardless of adhesive use, which generally agrees with previous studies [ 13 22 34 ]. Therefore, the null hypothesis was rejected because the moderate and low concentrations of hydrogel-based DAP and TAP medicaments did not cause clinically perceivable tooth discoloration at all measured time points regardless of the use of an adhesive bonding agent.…”
Section: Discussionsupporting
confidence: 92%
“…Color measurement was performed with the spectrophotometer, which has been used in many previous studies and provides reliable color determination. [14][15][16]20 A spectrophotometer provides color determination according to internationally accepted ISO standards by measuring according to the CIE color model. The ΔE value was calculated to observe the color change, and a value above 3.5 is the clinically visible difference.…”
Section: Discussionmentioning
confidence: 99%
“…15 Various methods have been studied to prevent tooth discoloration. [15][16][17][18] It has been reported that sealing the dentinal tubules of the pulp chamber with a bonding agent may be a suitable alternative to minimize tooth discoloration. 15 Another treatment option for sealing dentinal tubules is laser application; favorable results have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Teethmate is composed of two different types of calcium phosphate (tetracalcium phosphate and dicalcium phosphate anhydrous) which react with water to form hydroxyapatite. 36,37 Nupro bioactive glass is mainly composed of SiO 2 , Na 2 O, CaO, and P 2 O 5 . According to a study by Gupta et al, sodium release can increase the local pH and facilitate the deposition of additional phosphate and calcium ions.…”
Section: Discussionmentioning
confidence: 99%